Preparasi dan Karakterisasi Nanosuspensi dengan Polivinilpirolidon (PVP) Sebagai Pembawa Nanopartikel Senyawa Asam Mefenamat - Iskandarsyah, Iskandarsyah; Mutakim, Alip (UI Scholars Hub, 2010)
Several methods and technologies to increasing the solubility and dissolution rate of a drug substance has been successfully developed, such as forming of a complexing compound, salt preparation, adjusting the pH, making of solid dispersions, etc. One of the technologies that are being developed is nanoparticle technology. Micronization of drug that is processed to produce particles with nano-size. This research aims to create and characterize nanosuspension with Polyvinylpyrrolidone (PVP) as the vehicle of mefenamic acid nanoparticles using vibrating mill and ultrasound equipment. Nanosuspension obtained was characterized by optical microscope and PSA to perform optimization nanosuspension formed. The result of characterization showed that the nanosuspension have an average diameter is 623.9 nm. Then, nanosuspension of mefenamic acid was freeze drying. Nanosuspension and bulk of mefenamic acid were characterization by XRD and put in a hard capsule shell for dissolution test. Profile of dissolution test with tris buffer media indicates that nanosuspension of mefenamic acid has a pattern of drug release is slower and constant compared with the mefenamic acid. bulk.